EFFICACY OF READING COMPREHENSION MODELS IN SCHEMA DEVELOPMENT PROCESS - AN EMPIRICAL INVESTIGATION - Shehar Bano; Dr Maimoona Abdulaziz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This experimental study aimed at evaluating the reading comprehension strategies and vocabulary learning techniques through the lens of schema development in learners. The focus of this research work is on learning new lexis by comparing the efficacy of top-down and bottom-up models of reading comprehension. The study further discloses the details of how learners develop the understanding by using previous experiences and background knowledge. In order to justify the main aim of the research a mixed method research framework was adopted for data collection process. Data has been collected from 20 students of 8th grade. The current research is having both qualitative and quantitative bent. Due to the experimental structure of the research, data collection process relied on pre-test and post-test of vocabulary and reading comprehension. SPSS software has been used for quantitative data analysis. Qualitative data has been analyzed on the basis of research questions which this research is based on. This research may help ESL instructors to guide students with a wholesome analysis of reading strategies, which assist them in comprehension process in order to read according to the context. By equating both models of reading comprehension on the basis overall data the results show that top-down reading comprehension approach is more operative in schema activation process as oppose to the bottom-up approach. The article is significant in developing new methods and techniques for English language pedagogy. Comparison of two distinct models of reading comprehension highlights their pros and cons, which may be used further for an improvised practice of teaching English vocabulary.